GAMBARAN PENGELOLAAN LIMBAH BERBAHAYA DAN BERACUN DI RUMAH SAKIT UMUM DAERAH PARIAMAN TAHUN 2021 - Azhar, Aulia; Zeswita, Armein Lusi (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Sources of waste in hospitals can come from medical activities, nursing, dentistry, veterinary medicine, drug manufacturing or training, treatment, research, processing, teaching and research activities as well as from blood collection activities through transfusion. These activities can pose a great risk of disease transmission. Seeing so many activities that pose a risk to the surrounding environment, it is necessary to properly and safely manage waste. Waste management must be addressed immediately to ensure the health and safety of workers and other people in the hospital environment. For this reason, policies are needed according to occupational health and safety management by carrying out management and monitoring activities of hospital waste as one of the important indicators that need to be considered. This research to find out the description of the transportation of B3 Waste in Pariaman Hospital. The research design used in the descriptive survey research with a qualitative approach in the form of interviews and observations to obtain an overview of B3 waste management at the Pariaman Regional General Hospital in 2021. The object being studied is the infectious B3 waste management carried out by Pariaman Hospital. Infectious B3 Waste Management carried out at the Pariaman Regional General Hospital is in accordance with the requirements stated in the Regulation of the Minister of Environment and Forestry of the Republic of Indonesia Number P.56 of 2015 starting from B3 waste sorting, B3 waste storage, B3 waste transportation.